Asymmetric and nonlinear pass-through of energy prices to CO2 emission allowance prices - Hammoudeh, Shawkat (2014)
We use the recently developed nonlinear autoregressive distributed lags (NARDL) model to examine the pass-through of changes in crude oil prices, natural gas prices, coal prices and electricity prices to the CO2 emission allowance prices. This approach allows one to simultaneously test the short- and long-run nonlinearities through the positive and negative partial sum decompositions of the predetermined explanatory variables. It also offers the possibility to quantify the respective responses of the CO2 emission prices to positive and negative shocks to the prices of their determinants from the asymmetric dynamic multipliers. We find that: (i) the crude oil prices have a long-run negative and asymmetric effect on the CO2 allowance prices; (ii) the falls in the coal prices have a stronger impact on the carbon prices in the short-run than the increases; (iii) the natural gas prices and electricity prices have a symmetric effect on the carbon prices, but this effect is negative for the former and positive for the latter. Policy implications are provided.